Development of Tempeh Flour and Purple Sweet Potato-Based Cookies (TUBIC) Rich in Branched-Chain Amino Acids (BCAAs) and Antioxidants - An-nisa Visi Asmara; Khantsa Mastura; ⁠Dwi Sarbini (PT FORMOSA CENDEKIA GLOBAL, 2026)
Branched-Chain Amino Acids (BCAAs), consisting of leucine, isoleucine, and valine, are essential amino acids that play important roles in protein synthesis, maintenance of muscle mass, and improvement of nutritional status. Tempeh, a traditional fermented soybean product, is a potential source of BCAAs, protein, isoflavones, and other bioactive compounds. However, the relatively short shelf life of fresh tempeh necessitates processing innovations to produce food products that are more practical and have longer storage stability. This study aimed to develop cookies formulated from tempeh flour and purple sweet potato as a functional food rich in BCAAs and antioxidants. The developed product is expected to serve as a nutritious snack alternative that supports nutritional requirements and contributes to improved quality of life, particularly among individuals with increased protein and antioxidant needs. The study also evaluated the physical, chemical, and sensory characteristics of the formulated cookies. A Completely Randomized Design (CRD) with three formulations was employed. The moisture contents of Formula 1 (F1), Formula 2 (F2), and Formula 3 (F3) were 11.58%, 8.93%, and 9.18%, respectively. Color analysis showed variations in L*, a*, and b* values among formulations, while sensory evaluation revealed no significant differences in consumer acceptance between formulations. Extended baking time is recommended to further reduce moisture content and improve product quality and shelf-life stability.